Water Retention and Saturation Degree of Peat Soil in Sebangau Catchment Area, Central Kalimantan - Sajarwan, Akhmat; Jaya, Adi; Banuwa, Irwan Sukri (JOURNAL OF TROPICAL SOILS, 2021)
Water is an essential factor in forming, utilization, management, and sustainability of peat soil. This study was to obtain characteristics of water retention and porosity of peat soil. Peat samples were taken from the Natural Laboratory of Peat Forest, Central Kalimantan at shallow, medium, and deep peat at 0-50cm (surface) and 50-100 cm (subsurface), while laboratory analyses carried out at Soil Laboratory, Universitas Gajahmada. The result shows that volumetric moisture content at the surface lower than subsurface, except for deep peat. The total pore for the surface was 84.67-86.98%, while subsurface layers were 83.53-86.93%. For surface layer, saturated degree (S) medium peat higher than shallow and deep peat, while for shallow subsurface peat higher than medium and deep peat. S value all pF levels of surface for medium and deep peat higher than the subsurface. Bulk density for surface was 0.094g.cm-3 (rb(wet)) and 0.22g.cm-3(rb (dry)) for shallow peat while medium peat are 0.084–0.087g.cm-3(rb(wet)) and 0.18–0.20g.cm-3(rb(dry)), deep peat 0.064–0.090g.cm-3(rb(wet)) and 0.11–0.16g.cm-3(rb(dry)). For subsurface, bulk density of medium peat are 0.094–0.107g.cm-3 (rb(wet)) and 0.16–0.20g.cm-3 (rb(dry)), deep peat are 0.067–0.090g.cm-3 (rb(wet)) and 0.10–0.17g.cm-3 (rb(wet)). The particle density of surface and subsurface for shallow peat higher than medium and deep peat, with values 0.67-0.77g.cm3, 0.61-0.66g.cm3, and 0.53-0.63g.cm3 for shallow, medium, and deep peat, respectively. Total pores for the surface layer decrease with increasing dry bulk density (R = 0.624) and particle density (R = 0.375). This fact seems to confirm a directly proportional relationship between parameters bulk and particle density with total pores.